Human rights in Chinese foreign policy: a battle for global public opinion - Kinzelbach, Katrin (Edward Elgar Publishing Ltd., 2019)
This chapter reviews from when, why and how human rights have played a role in the foreign policy of the People’s Republic of China. Until 1988, human rights did not figure prominently in Chinese diplomacy. From 1989 onwards, as a result of an international outcry against the violent crackdown of peaceful demonstrations, the Party-state initially employed a defensive rhetoric that focused on downplaying human rights violations. Beijing’s diplomats offered to engage in confidential dialogues and signaled goodwill by making a number of calculated concessions. As memories of the massacre faded and global power dynamics shifted, the Party-state’s international stance on human rights became more assertive. This chapter argues that the People’s Republic successfully used a combination of propagandistic communications and tools of power politics to immunize itself against international human rights criticism.
CRIS-Team Scopus Importer:2023-03-21